Designing and Development of an Oral Health Educational Game and Evaluation of Its Effect on 8-12-Year-Old Children’s Oral Health: A Randomized Clinical Trial - Nourian, Azin; Motamed , Nima; Samanipour, Marzieh (Journal of Dental School, 2021)
Objectives Health education for school-age children is a specialized component of the oral health promotion program. This study aimed to design and develop an oral health educational game and assess its effect on the oral health of children aged 8 to 12 years. Methods In this experimental study, 40 patients aged 8-12 years referring to a private dental clinic were selected by using convenience sampling and were then randomly assigned to the experimental and control groups. The experimental group received oral health training by using a game; while, the control group received oral hygiene instructions. The simplified oral hygiene index (OHI-S) with two components of debris index (DI-S) and calculus index (CI-S) was measured before the intervention, and at one week, and one month after the intervention to assess the effect of oral health skills. Data were analyzed by the Chi-square test, independent sample t-test, and Fisher’s exact test. Results The DI-S scores in the experimental group at one week and one month after the intervention were significantly lower than the values in the control group (P=0.003 and P=0.001, respectively). The OHI-S scores in the experimental group at one week and one month after the intervention were significantly lower than the values in the control group (P=0.012 and P=0.007, respectively). No significant difference was noticed in the follow-up CI-S scores at one week and one month after the intervention (P>0.05). Conclusion The game designed in this study would improve the children’s oral health skills; hence, it can be used to promote oral health in children.